2019
DOI: 10.5296/jas.v7i2.14788
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit Analysis of Seedling Production on Floating Beds in a Few Selected Areas of Bangladesh

Abstract: The aim of this study was to calculate the cost benefit analysis and economic viability of seedling production on the floating bed at Nazirpur Upazila in Pirojpur district of Bangladesh. The study area was selected purposively and 50 households (HHs) were surveyed through purposive sampling technique from a population of 80 households. From the results of those primary data, it was found that 68% farmers were engaged in seedling production as business purpose, and 30% as both own and business, 21 vegetables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Socio-economic profile of farmers Demographic statistics (Table 1) reveals that about 54% of the floating gardeners were middle aged (35-50). Similar to the findings of Pavel et al (2014) and Kabir et al (2019), about 68% of the respondents was found literate. It indicates that floating gardeners were educated.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Socio-economic profile of farmers Demographic statistics (Table 1) reveals that about 54% of the floating gardeners were middle aged (35-50). Similar to the findings of Pavel et al (2014) and Kabir et al (2019), about 68% of the respondents was found literate. It indicates that floating gardeners were educated.…”
Section: Resultssupporting
confidence: 89%
“…Average marginal, small and medium farm size was 0.16, 0.73 and 1.27 hectare, respectively. More involvement of marginal (21%) and small farmers (56%) in floating gardening signifies the importance of this practice as an alternative source of income to them (Alam and Chowdhury, 2018;Kabir et al, 2019). Analysis of the housing pattern also reveals a typical scenario of resource poor people (Irfanullah, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations